Effects of silver sulfide quantum dots coated with 2-mercaptopropionic acid on genotoxic and apoptotic pathways in vitro. (1st August 2018) - Ozkan Vardar, Deniz; Aydin, Sevtap; Hocaoglu, Ibrahim; Yagci Acar, Funda Havva; Basaran, Nursen
Abstract: Quantum dots (QDs) are highly promising nanomaterials in bioimaging system because of their bright fluorescence, broad UV excitation, narrow emission band, and high photostability. Recently, there is a great activity on Ag2 S quantum dots for both imaging and drug/gene delivery due to the potential of having a better cytocompatability and near infrared luminescence. 2-Mercaptopropionic acid (2 MP A)-coated silver sulfide (Ag2 S) QDs were reported as the most luminescent, stable, anionic Ag2 S QDs in the literature. In this study, we aim to determine the cytotoxicity of 2 MP A/Ag2 S in Chinese hamster lung fibroblast (V79) cells. The genotoxic and apoptotic effects of 2 MP A/Ag2 S QDs were assessed by the alkaline single cell electrophoresis assay and real time polymerase chain reaction techniques, respectively. The cell viability decreased above 200 μg/ml and 800 μg/ml for MTT tetrazolium and neural red uptake assays, respectively. DNA damage was not observed by 2 MP A/Ag2 S QDs at the studied concentration levels (5–2000 μg/ml). The levels of mRNA expression of p53, caspase 3, caspase 9, bax, bcl-2, survivin were not changed by 2 MP A/Ag2 S QDs below IC50 (around 1000 μg/ml). Hence, 2 MP A/Ag2 S QDs did not show any cytotoxic or genotoxic effects in V79 cells at lower doses. We conclude that the biocompatibility of 2 MP A/Ag2 SODs makes them suitable for cell labeling applications. Highlights: IC50 of 2 MPA/Ag2 S QDs was around 1000 μg/ml in V79 cells. DNA integrity was not affected by 2 MPA/Ag2 SQDs below 2000 μg/ml. 2 MPA/Ag2 S QDs did not change apoptosis at concentrations below IC50 2 MPA/Ag2 S QDs did not show any cytotoxic or genotoxic effects. 2 MPA/Ag2 S ODs is biocompatible in V79 cells.